The Effects of Surgery on Postural Instability in Patients With Cervical Compressive Myelopathy: Evaluating Subjective Perceptions and Objective Measurements. Issue 2 (March 2022) - Yano, Toma; Fujishiro, Takashi; Obo, Takuya; Nakano, Atsushi; Nakaya, Yoshiharu; Hayama, Sachio; Mori, Katsunori; Baba, Ichiro; Neo, Masashi
Abstract : Study Design: A retrospective study. Objective: To investigate the effects of surgery on the subjective perception of bodily unsteadiness and the objective measurements of postural instability in patients with cervical compressive myelopathy (CCM). Summary of Background Data: Several studies have demonstrated that CCM patients have impaired postural stability and investigated its surgical outcomes. However, these studies have only objectively measured postural stability by using a stabilometer or three-dimensional motion capture system. There have been no studies examining the subjective perception of postural instability in CCM patients. Materials and Methods: We retrospectively reviewed patients who underwent decompressive surgery for CCM. The Fall Efficacy Scale-International (FES-I) and a self-prepared questionnaire were used to evaluate subjective perception of bodily unsteadiness. To objectively assess postural instability, a stabilometric analysis was performed with the following parameters: sway area (SwA, cm 2 ), sway velocity (SwV, cm/s), and sway density (SwD, /cm). The evaluations were performed preoperatively, during the early postoperative period (3–6 mo postoperatively), and at 1-year postoperatively in patients with CCM. The evaluation results were compared with age-matched, sex-matched, and body mass index-matched healthy subjects. Results: We included 70 CCM patients and 36 healthy subjects in this study. In both the FES-I and self-prepared questionnaire, CCM patients reported significantly milder postoperative bodily unsteadiness. The stabilometric parameters were significantly improved during the postoperative period when compared with preoperative values. Nevertheless, neither the self-reported outcome measures nor stabilometric parameters of CCM patients reached the levels of those in healthy controls in the postoperative period. Conclusion: This was the first study to examine CCM surgical outcomes in terms of both subjective perception and objective postural instability. While both objective postural stability and subjective perception improved following decompressive surgery, they did not reach the levels seen in healthy participants. Level of Evidence: Level III.